Survival improvement in primary plasma cell leukemia: a retrospective analysis of novel agent-based regimens and stem cell transplantation - Xu, Yong; He, Jie; Chen, Lanxin; Liu, Jinwen; Zhou, Min; Chen, Bing; Bai, Hua (Frontiers in Oncology, 2026)
BackgroundThis study aimed to characterize the clinical profile and treatment outcomes of primary plasma cell leukemia (pPCL) patients, defined by ≥5% circulating plasma cells (CPCs) on peripheral blood smear, who received novel agent-based induction therapy.MethodsA retrospective analysis of 46 pPCL patients treated at Nanjing Drum Tower Hospital from March 2014 to April 2025 was conducted. Their clinical and laboratory manifestations, prognostic factors, and efficacy of induction therapies were focused upon.ResultsAdvanced-stage disease predominated in our cohort. The most frequent cytogenetic abnormalities were chromosome 1q21+ and del(13q14). Failure to achieve ≥very good partial response (VGPR) after first-line therapy independently predicted inferior overall survival (OS) (HR = 0.095, 95%CI 0.022-0.421, p = 0.002) and shorter median time to next therapy (TTNT) (HR = 0.088, 95%CI 0.024-0.329, p<0.001). Intensified regimens combining proteasome inhibitors (PIs)/immunomodulatory drugs (IMiDs) with venetoclax (Ven) significantly improved ≥VGPR rates, particularly when followed by autologous stem cell transplantation (ASCT), prolonged median OS.ConclusionDespite novel agents, pPCL maintains poor prognosis, with treatment failure strongly associated with suboptimal first-line response. Therapeutic intensification through PIs/IMiDs with Ven (guided by t(11;14)) and ASCT consolidation may enhance depth of remission and survival outcomes.